The potential of intervening on childhood adversity to reduce socioeconomic inequities in body mass index and inflammation among Australian and UK children: A causal mediation analysis - Priest, Naomi; Guo, Shuaijun; Gondek, Dawid; O'Connor, Meredith; Moreno-Betancur, Margarita; Gray, Sarah; Lacey, Rebecca; Burgner, David P; Woolfenden, Sue; Badland, Hannah; Redmond, Gerry; Juonala, Markus; et al. (My University, 2023)
Background: Lower maternal education is associated with higher body mass index (BMI) and higher chronic inflammation in offspring. Childhood adversity potentially mediates these associations. We examined the extent to which addressing childhood adversity could reduce socioeconomic inequities in these outcomes. Methods: We analysed data from two early-life longitudinal cohorts: Longitudinal Study of Australian Children (LSAC; N=1873) and the UK Avon Longitudinal Study of Parents and Children (ALSPAC; N=7085). Exposure: Low/medium (below university degree) versus high maternal education, as a key indicator of family socioeconomic position (0-1 year). Outcomes: BMI and log-transformed Glycoprotein acetyls (GlycA) (LSAC: 11-12 years; ALSPAC: 15.5 years). Mediator: multiple adversities (≥2/<2) indicated by family violence, mental illness, substance abuse, and hash parenting (LSAC: 2-11 years; ALSPAC: 1-12 years). Causal mediation analysis was conducted. Results: Low/medium maternal education was associated with up to 1.03 kg/m2 higher BMI (95% CI: 0.95, 1.10) and up to 1.69% higher GlycA (95% CI: 1.68, 1.71) compared with high maternal education, adjusting for confounders. Causal mediation analysis estimated that decreasing the levels of multiple adversities in children with low/medium maternal education to be like their high maternal education peers could reduce BMI inequalities by up to 1.8% and up to 3.3% in GlycA. Conclusions: Our findings in both cohorts suggest that slight reductions in socioeconomic inequities in children’s BMI and inflammation could be achieved by addressing childhood adversities. Public health and social policy efforts should help those affected by childhood adversity, but also consider underlying socioeconomic conditions that drive health inequities.
Journal of Epidemiology and Community Health
Keywords: CARDIOVASCULAR DISEASES; CHILD HEALTH; Health inequalities; LONGITUDINAL STUDIES; PUBLIC HEALTH; Adolescents and youth; Disadvantage, adversity and resilience; Childhood and child development